Platform Capitalism and Uneven Digital Transformation: Organizational Constraints in Social Media–Based Property Marketing in Indonesia - Mohammad Mutohar; Fajar Pasaribu (Baileo: Jurnal Sosial Humaniora, 2026)
This study examines platform capitalism and uneven digital transformation in social media–based property marketing in Indonesia, focusing on organizational constraints that shape marketing practices. While digital transformation is often framed as a linear path to efficiency and increased sales, this study argues that in the Global South it is inherently uneven, mediated by platform logics and internal organizational limitations. A qualitative descriptive approach was employed through in-depth interviews, observations, and document analysis involving key informants from a property company in North Sumatra. Data were analyzed using an interactive model supported by triangulation. The findings show that social media platforms function not only as promotional tools but also as market infrastructures mediating early interactions between firms and consumers. Visual content operates as symbolic capital shaping consumer perception and engagement. However, digital marketing effectiveness is constrained by limited human resources, inadequate content production, and the absence of an integrated Customer Relationship Management system, resulting in fragmented implementation. This indicates that digital transformation remains partial and uneven at the organizational level, reinforcing dependence on platform algorithms. This study contributes by reconceptualizing digital marketing as a platform-mediated social practice and identifying organizational constraints as a key locus of digital inequality. It recommends strengthening digital capacity, integrated systems, and community-based digital literacy to support inclusive and sustainable development.